REVITALISASI MANAJEMEN SDM DALAM LEMBAGA PENDIDIKAN ISLAM: PERSPEKTIF MOTIVASI DAN KEPUASAN KERJA - Azka Alfi Nurus Sa’adah; Sulistyorini Sulistyorini (STKIP Pesisir Selatan, 2026)
This study aims to analyze the revitalization of human resource management (HRM) in Islamic educational institutions by focusing on strategies that strengthen work motivation and job satisfaction among educators. This research employed the library research method by reviewing reputable and up-to-date literature from 2019–2024, including national and international journal articles, books, and relevant research reports. The analysis process involved content analysis, identification of emerging themes, and synthesis of literature related to HRM strategies, motivation, and job satisfaction in the context of Islamic education. The study found that effective HRM in Islamic educational institutions is characterized by continuous professional development, Islamic-based organizational culture, academic supervision, and equitable compensation systems. Motivation is influenced by intrinsic factors such as spirituality, sincerity, leadership style, and communication, while extrinsic factors include rewards, career development, and workplace environment. Job satisfaction is shaped by emotional responses to work, fairness perception, organizational support, and career advancement opportunities. This research offers an integrative model linking Islamic values with HRM strategies to enhance educator motivation and satisfaction—an aspect that has been underexplored in recent five-year studies. The findings highlight the importance of combining professionalism with Islamic spirituality to build competitive and sustainable Islamic educational institutions.